If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -1) = 5(x + 3) Reorder the terms: 6(-1 + 2x) = 5(x + 3) (-1 * 6 + 2x * 6) = 5(x + 3) (-6 + 12x) = 5(x + 3) Reorder the terms: -6 + 12x = 5(3 + x) -6 + 12x = (3 * 5 + x * 5) -6 + 12x = (15 + 5x) Solving -6 + 12x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 12x + -5x = 15 + 5x + -5x Combine like terms: 12x + -5x = 7x -6 + 7x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + 7x = 15 + 0 -6 + 7x = 15 Add '6' to each side of the equation. -6 + 6 + 7x = 15 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 15 + 6 7x = 15 + 6 Combine like terms: 15 + 6 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| (x+6)(x-6)(2x-5)=0 | | 5(a+4)=4(a-3) | | 5(2x+3)=25 | | 4X-40=12+6X-6X | | -3(p-4)=21 | | 3(2t+1)=21 | | 5(m-4)=35 | | 2(4x-3)=30 | | (1/4)x-1=7 | | 9x-2=4(x+3) | | 2x+y+3yi=5-xi | | 3x^2-21x+21=x^2-4x | | y=4*10 | | 0.20x+0.5(4-x)=.10(5) | | 120=90 | | 9(105)+3(104)+5(103)+3(102)+7(101)=1 | | -133+5x=101+14x | | -3(y+1)=15 | | -2(3x-1)=20 | | 6(x-2)=28 | | 27x+x=135 | | 2(5x-1)=28 | | -29-2x=-4x+51 | | 8(2x-1)=64 | | t=2g+2v | | 7(m-4)=14 | | 3(y+1)=15 | | 6(3m-2)=2(2m+1) | | 4y=7y-27 | | -249-6x=-17x+70 | | 10x-2=14+2x | | 3(3y-2)=21 |